Integration of phase-field model and crystal plasticity for the prediction of process-structure-property relation of additively manufactured metallic materials. (May 2020) - Liu, P.W.; Wang, Z.; Xiao, Y.H.; Lebensohn, R.A.; Liu, Y.C.; Horstemeyer, M.F.; Cui, X.Y.; Chen, L.
Abstract: A computational framework is developed to investigate the process-structure-property relationship for additive manufacturing (AM) of Ti–6Al–4V alloy. The proposed model incorporates experimentally informed two-phase α+β morphologies within prior β-grains, which are widely observed in the as-built AM components. Specifically, the temperature-dependent phase-field model (PFM) is used to simulate the evolution of various grain morphologies, e.g., columnar and equiaxed grain structures. The proposed PFM taking into account both of the epitaxial grain growth and the constitutional cooling-driven heterogeneous nucleation enables us to capture the columnar to equiaxed transition (CET) of grain structures. The thermal fields concerned with the scanning strategies and manufacturing parameters are simulated using a finite-element model (FEM). The Burgers orientation relation (BOR) is further utilized to generate two-phase α+β morphologies within prior β-grains, accompanied by the transformation of crystal orientations, i.e., (0001)α //{101}β and < 11 2 ‾ 0 >α //<111>β . Finally, a fast Fourier transform-based elasto-viscoplastic (EVP-FFT) model is employed to predict the micromechanical behaviors and properties for the two-phase α+β microstructures. The presented PFM-based formulation is generally applicable to predict the process-structure-property relationship for additive manufacturing of a variety of alloy systems, e.g., titanium alloys, aluminum alloys and nickel-based superalloys. Highlights: Two-phase lamellar α+β morphology for Ti–6Al–4V are considered in the computational framework. High travel speed and low power provide the equiaxed β-grain structures and fine α-lath microstructures. Equiaxed β-grain structures provide higher tensile strength than that of columnar β-grain structures due to shorter effective slip length. Fine α-lath microstructure and small colony size reduce the effective slip length, and thus provide high tensile strength. Stress concentrations due to dislocation pile-ups induce the crack and thus reduce the ductility of columnar β-grains in R x -direction.